2023
DOI: 10.3390/genes14020444
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Hypothalamic Transcriptome Analysis Reveals Crucial mRNAs, lncRNAs, and circRNAs Affecting Litter Size in Goats

Abstract: Litter size is an important indicator to measure the reproductive performance of goats, which is affected by the reproductive function of animals. The hypothalamus, as the regulatory center of the endocrine system, plays an important role in the reproduction of female animals. Here, we performed high-throughput RNA sequencing using hypothalamic tissue from high-fecundity and low-fecundity Leizhou goats to explore critical functional genes associated with litter size. Differentially expressed mRNA, lncRNA, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Additionally, leptin inhibits uterine contractions in mice by stimulating the JAK-STAT signaling pathway [46]. The characterization of miRNA and mRNA expression profiles in hypothalamic tissues of high-and low-follicular fertility goats reveals that the identified differential expressed genes are significantly enriched in the JAK-STAT signaling pathway [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, leptin inhibits uterine contractions in mice by stimulating the JAK-STAT signaling pathway [46]. The characterization of miRNA and mRNA expression profiles in hypothalamic tissues of high-and low-follicular fertility goats reveals that the identified differential expressed genes are significantly enriched in the JAK-STAT signaling pathway [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The GRM1 gene, which was previously identified in a CNV study in American mink 64 , was located within the duplication CNVR15 (Chr1: 56,870,177–56,925,961), associated with AWB trait. The GRM1 was a gene of interest reported in several studies to be associated with female reproduction in different livestock species, such as seasonal reproduction in sheep 79 , litter size in goats 80 , number of teats and litter traits in pig 81 , and fertility-related traits in cattle 82 . Interestingly, it was reported that the GRM1 gene located within structural variations and runs of homozygosity regions associated with litter traits in pigs 83 , 84 , highlighting the hypothesis that this gene might be a candidate gene for female reproduction in American mink.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that lncRNA Meg3 can regulate the expression of GnRH and Kiss-1 in hypothalamic cells, and knockdown of lncRNA Meg3 can delay puberty in female rats ( 16 ). Additionally, the lncRNA MSTRG.33887.2 has the potential to influence goat reproduction by regulating target genes involved in hypothalamic folate metabolism and energy metabolism homeostasis ( 17 ). Mouse hypothalamic lncRNA AK044061 plays a crucial role in energy balance by mediating NF-kβ.…”
Section: Introductionmentioning
confidence: 99%